Documentation of time-scales for onset of natural attenuation in an aquifer treated by a crude-oil recovery system - Ponsin, Violaine; Maier, Joachim; Guelorget, Yves; Hunkeler, Daniel; Bouchard, Daniel; Villavicencio, Hakeline; Höhener, Patrick (My University, 2015)
A pipeline transporting crude-oil broke in a nature reserve in 2009 and spilled 5100 m3 of oil that partly reached the aquifer and formed progressively a floating oil lens. Groundwater monitoring started immediately after the spill and crude-oil recovery by dual pump-and-skim technology was operated after oil lens formation. This study aimed at documenting the implementation of redox-specific natural attenuation processes in the saturated zone and at assessing whether dissolved compounds were degraded. Seven targeted water sampling campaigns were done during four years in addition to a routine monitoring of hydrocarbon concentrations. Liquid oil reached the aquifer within 2.5 months, and anaerobic processes, from denitrification to reduction of sulfate, were observable after 8 months. Methanogenesis appeared on site after 28 months. Stable carbon isotope analyses after 16 months showed maximum shifts in δ13C of + 4.9 ± 0.22‰ for toluene, + 2.4 ± 0.19‰ for benzene and + 0.9 ± 0.51‰ for ethylbenzene, suggesting anaerobic degradation of these compounds in the source zone. Estimations of fluxes of inorganic carbon produced by biodegradation revealed that, in average, 60% of inorganic carbon production was attributable to sulfate reduction. This percentage tended to decrease with time while the production of carbon attributable to methanogenesis was increasing. Within the investigation time frame, mass balance estimations showed that biodegradation is a more efficient process for control of dissolved concentrations compared to pumping and filtration on an activated charcoal filter.
Keywords: La Crau nature reserve; Benzene; Hydrocarbon spill; Aquifer; Biodegradation; Stable carbon isotopes